Investment in human capital : company expenditures on continuing vocational training in times of technological change in Germany - Baum, Myriam [Verfasser]; Fournier, Lisa [Verfasser] (My University, 2023)
"Context: The scientific and political discourse often acclaims continuing training as the key for adapting to today's changes in the labour market, caused – among others– by technological change. However, changed skill demand and increased continuing training participation does not necessarily translate into increased investment in human capital by employers, especially for already disadvantaged skill groups. Therefore, this analysis focusses on the relation between companies’ investment in human capital, technological change indicators and companies’ skill structure. Methods: We use quantitative data from the 2020 wave of a representative establishment survey for Germany to estimate ordinary least square regressions. Results: The results show that the investment in technology and the technology level positively relate to investment in human capital. However, the an above average share of low-skilled employees is negatively associated with a companies’ human capital investment. Conclusion: Investment in technology and the technology level do lead to an increase in human capital investment. Still, the skill structure in a company is important for determining whether companies invest in the human capital of their employees. Combined with the fact that most training is financed by the employer, increased investment by companies in times of technological change could lead to increased or persistent barriers to continuing training for already disadvantaged groups. Therefore, further research in this area is needed. These findings provide a good starting point for policies aimed at reducing these barriers and increasing human capital investment for disadvantaged groups.“ (Authors‘ abstract; BIBB-Doku)
Keywords: S 1.5.3 Betriebliche Weiterbildung; S 4.3.6 Human Capital; 370; Betriebliche Weiterbildung; Bildungsinvestition; Humankapital; Betrieb; Einflussfaktor; Technischer Wandel; Digitalisierung; Qualifikationsstruktur; Betriebsbefragung